PENGGUNAAN LUMPUR LAUT CAIR PADA TANAH GAMBUT UNTUK MENINGKATKAN SIFAT KIMIA TANAH - Andrayani, Ketti (Institute of Computer Science (IOCS), 2025)
The development and utilization of peat soil as a plant growing medium cannot be separated from limiting factors, one of which is the chemical properties of peat, namely low pH, very high cation exchange capacity (CEC) with very low base saturation (KB), and low macro and micro nutrients, resulting in low soil fertility and inhibited nutrients for plants. The provision of ameliorant in the form of sea mud is one alternative to improve the chemical properties of peat. The use of sea mud as a soil conditioner can improve the chemical properties of peat considering its high base content such as Calcium (Ca), Magnesium (Mg), Sodium (Na) and Potassium (K) cations. The high base content in sea mud can improve nutrient availability, low pH availability, can increase base saturation and reduce the high cation exchange capacity in peat soil. Improvement of peat soil characteristics with the addition of sea mud ameliorant can affect peat soil fertility. The purpose of this study was to study and analyze the role of sea mud in improving the chemical properties of peat. This study uses descriptive analysis by testing laboratory data of liquid sea mud. The parameters used in this study are soil pH, base saturation, cation exchange capacity, Sodium, Calcium, Potassium and Magnesium. The provision of sea mud on peat soil is given at a level of 5% and 7.5% on 10 kg of peat soil. The use of sea mud at a level of 7.5% gives better results in terms of decreasing the value of cation exchange capacity, increasing pH, increasing base saturation, increasing sodium, potassium, calcium and magnesium elements. Initial analysis of initial soil pH ranges from 3.37, KB 7.74% and CEC 119.66 cmol (+) kg-1, Sodium content 0.6 cmol (+) kg-1, calcium 5.37 cmol (+) kg-1, potassium 0.37 cmol (+) kg-1, and Magnesium 2.87 cmol (+) kg-1. But after the treatment of 7.5% sea mud there was an increase in pH to 3.54, KB 17.49% and CEC 112.29 cmol (+) kg-1, Magnesium 10.72 cmol (+) kg-1, Calcium 7.20 cmol (+) kg-1, and Sodium 0.66 cmol (+) kg1. The results of the study showed that the provision of sea mud on peat soil can improve the chemical properties of peat, especially the provision of sea mud at a level of 7.5%. This proves that the use of sea mud has great potential in improving the limiting factors found in peat soil.